Evaluation of Obesity Influence in the Sexual Function of Postmenopausal Women: A Cross-Sectional Study - Silva, Gustavo Maximiliano Dutra da; Lima, Sônia Maria Rolim Rosa; Reis, Benedito Fabiano dos; Macruz, Carolina Furtado; Postigo, Sóstenes (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The incidence of obesity, which is a chronic condition, has increased in recent years. The association between obesity and female sexual dysfunction remains unclear, particularly in postmenopausal women. In the present study, we evaluated whether obesity is a risk factor for sexual dysfunction in postmenopausal women.Methods This is a cross-sectional study that analyzed data from interviews of postmenopausal women at the Climacteric Outpatient Clinic from 2015 to 2018. After applying the inclusion and exclusion criteria, 221 women aged between 40 and 65 years old were selected and invited to participate in the study. Obesity was diagnosed according to body mass index (BMI). The participants were grouped into the following BMI categories: group 1, 18.5–24.9 kg/m2 (normal); group 2, 25.0–29.9 kg/m2 (overweight); and group 3, ≥30.0 kg/m2 (obese). Sexual function was assessed using the Female Sexual Function Index (FSFI) questionnaire. Cutoff points of ≥23 and ≥26.5 were adopted to define a diagnosis of female sexual dysfunction (FSD) based on the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, Text Revision by the American Psychiatric Association (DSM-IV-TR).Results The desire and arousal scores were statistically higher in the normal BMI group than in the obese group (p = 0.028 and p = 0.043, respectively). The satisfaction scores were statistically higher in the normal BMI group than in the overweight and obese groups (p < 0.05). The total FSFI score statistically differed among the BMI categories (p = 0.027).Conclusion In the present study, obese and overweight postmenopausal women had higher total scores than women with normal BMI. Our results show that obese and overweight postmenopausal women had a higher index of dysfunction in desire and arousal and lower sexual satisfaction than normal-weight women.
Keywords: obesity; metabolic syndrome; body mass index; menopause; female sexual dysfunction